Design of a Marriage Service Management Application at the Pasar Jambi Religious Affairs Office - Suroto, Suroto; Syah , Tamrin (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The Office of Religious Affairs of the Pasar Jambi sub-district of Jambi City has several important tasks in terms of marriage affairs. Still, the problem is that the data is complex and not properly organized. Data speed is the answer for every person or resident in Jambi City. Those who want to get married have to go through a lot of documents that must be neatly recorded so that the data can be retrieved quickly and easily. Not only focusing on marriage or nikah data, the Office of Religious Affairs of the Pasar Jambi sub-district also takes care of several other things. Some examples of records carried out are the recording of marriages, referrals, mosque guidance, zakat, waqf, and other social worship. The service management application system at the religious affairs office of the Pasar Jambi sub-district will be able to provide answers on the data speed side. This service management system is made easier to use by all officers at the religious affairs office of the Pasar Jambi sub-district.